Why Not the Best? : The First Fifty Years - Carter, Jimmy, 1924- (Book collections on Project MUSE., 1996)
This campaign autobiography was begun in late 1974 when Georgia governor Jimmy Carter's presidential ambitions were being undervalued by the national media. It was received by the public as a welcome affirmation of one candidate's bedrock faith in old-fashioned public service based on duty, honor, competence, and honesty. With almost one million copies sold, it would help to propel him into the White House. In compelling yet humble language, Carter details his personal history to that point of his life: his idyllic childhood in remote Plains, his hazing incident at Annapolis for refusing to sing "Marching through Georgia," his near-death experience aboard a Pacific-fleet submarine, his strong Christian underpinnings, the compassionate humor of his mother, Miss Lillian, and the stern taskmaster ethics of his father, Mr. Earl. In short, this is the story of one righteous Southerner's coming of age, a Main Street memoir anchored by no-nonsense style and homespun storytelling.